Antibacterial activity of faloak (Sterculia quadrifida) leaves extract - THERESIA IKA PURWANTININGSIH; BUDI PRASETYO WIDYOBROTO; YUSTINA YUNI SURANINDYAH; WAYAN TUNAS ARTAMA (Society for Indonesian Biodiversity, 2023)
Abstract. Purwantiningsih TI, Widyobroto BP, Suranindyah YY, Artama WT. 2023. Antibacterial activity of faloak (Sterculia quadrifida) leaves extract. Biodiversitas 24: 6613-6620. Restrictions on the use of antibiotics have made people start looking for alternatives to antibiotics, one of which is ingredients that come from nature. Faloak (Sterculia quadrifida R. Br) leaves are a source of secondary metabolites that have not been widely utilized. The aim of this study was to assess the antibacterial activity of faloak leaves extract in inhibiting Staphylococcus aureus (gram-positive bacteria) and Escherichia coli (gram-negative bacteria). Powdered faloak leaves were macerated with 96% ethanol solvent. After obtaining the crude extract, it was fractionated using the liquid-liquid method using methanol, hexane, distilled water and ethyl acetate as solvents. The crude extract of faloak leaves was then dissolved into several concentrations. The crude extract of faloak leaves and the fractions obtained were tested for antibacterial activity in vitro using the Kirby Bauer method against Staphylococcus aureus and Escherichia coli. The most active fraction in inhibiting the tested bacteria was then screened for bioactive compounds using instrument LC-HRMS. The results showed that faloak leaves extract and its fractions were able to inhibit Staphylococcus aureus and Escherichia coli bacteria. The ethyl acetate fraction was the most active fraction in inhibiting bacteria and the most occurring bioactive compounds appeared in LC-HRMS testing were luteolin, rutin and corchorifatty acid. The total flavonoid compound in the crude extract was 227.281 QE µg/mL and the highest i.e. 351.456 QE µg/mL total flavonoid compound was in methanol fraction.